Glycosaminoglycan-Protein Interactions and Their Roles in Human Disease - Shi, Deling; Sheng, Anran; Chi, Lianli (Frontiers in Molecular Biosciences, 2021)
Glycosaminoglycans (GAGs) are a family of linear and negatively charged polysaccharides that exist ubiquitously on the human cell surface as well as in the extracellular matrix. GAGs interact with a wide range of proteins, including proteases, growth factors, cytokines, chemokines and adhesion molecules, enabling them to mediate many physiological processes, such as protein function, cellular adhesion and signaling. GAG-protein interactions participate in and intervene in a variety of human diseases, including cardiovascular disease, infectious disease, neurodegenerative diseases and tumors. The breakthrough in analytical tools and approaches during the last two decades has facilitated a greater understanding of the importance of GAG-protein interactions and their roles in human diseases. This review focuses on aspects of the molecular basis and mechanisms of GAG-protein interactions involved in human disease. The most recent advances in analytical tools, especially mass spectrometry-based GAG sequencing and binding motif characterization methods, are introduced. An update of selected families of GAG binding proteins is presented. Perspectives on development of novel therapeutics targeting specific GAG-protein interactions are also covered in this review.